2018
DOI: 10.1158/0008-5472.can-17-1327
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Resistance in Breast Cancer Is Regulated by the EZH2–ERα–GREB1 Transcriptional Axis

Abstract: Resistance to cancer treatment can be driven by epigenetic reprogramming of specific transcriptomes in favor of the refractory phenotypes. Here we discover that tamoxifen resistance in breast cancer is driven by a regulatory axis consisting of a master transcription factor, its cofactor, and an epigenetic regulator. The oncogenic histone methyltransferase EZH2 conferred tamoxifen resistance by silencing the expression of the estrogen receptor α (ERα) cofactor GREB1. In clinical specimens, induction of DNA meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 36 publications
6
67
0
Order By: Relevance
“…Consistent with our hypothesis, we identified context-specific ERα-cofactor interactions: its interactions with GREB1, NRIP1, and GATA3 were only detected in MCF7P cells, and its interaction with NCOA5 and FOXA1 were stronger in TamR cells ( Figure 3D). Indeed, loss of interaction between ERα and GREB1 34 and overexpression of FOXA1 21 are known to associate with hormone resistance, further supporting the authenticity of our BioID data. Several AP1 family TFs were among the identified ERα-interacting proteins ( Figure 3D), we later on chose JUN to study AP1 function on GAIN enhancers, as it is a common component of JUN/FOS and JUN/JUN dimers 35 .…”
Section: Altered Interactions Between Erα and Gata3/ap1 And Their Binsupporting
confidence: 80%
“…Consistent with our hypothesis, we identified context-specific ERα-cofactor interactions: its interactions with GREB1, NRIP1, and GATA3 were only detected in MCF7P cells, and its interaction with NCOA5 and FOXA1 were stronger in TamR cells ( Figure 3D). Indeed, loss of interaction between ERα and GREB1 34 and overexpression of FOXA1 21 are known to associate with hormone resistance, further supporting the authenticity of our BioID data. Several AP1 family TFs were among the identified ERα-interacting proteins ( Figure 3D), we later on chose JUN to study AP1 function on GAIN enhancers, as it is a common component of JUN/FOS and JUN/JUN dimers 35 .…”
Section: Altered Interactions Between Erα and Gata3/ap1 And Their Binsupporting
confidence: 80%
“…TAM has been widely used for treatment of ER + breast cancers in the clinic . However, TAM resistance is a huge challenge for clinical practice, and promotes breast cancer metastasis and death . Our previous studies and those of others have shown that DLG5 acts as a tumour suppressor in breast cancer, and its expression is up‐regulated in Luminal type, but not basal‐like, breast cancer .…”
Section: Discussionmentioning
confidence: 97%
“…Despite the clear association between GREB1 and proliferation of breast cancer cells, expression of GREB1 has been correlated to better prognosis in ER+ breast cancer patients (16, 40). In a study that included only patients that received adjuvant tamoxifen monotherapy, higher GREB1 expression correlated with both prolonged disease-free survival and sensitivity to tamoxifen treatment (40).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clear association between GREB1 and proliferation of breast cancer cells, expression of GREB1 has been correlated to better prognosis in ER+ breast cancer patients (16, 40). In a study that included only patients that received adjuvant tamoxifen monotherapy, higher GREB1 expression correlated with both prolonged disease-free survival and sensitivity to tamoxifen treatment (40). Similarly, in an in vitro model of tamoxifen resistance, MCF7 cells that were resistant to tamoxifen treatment had significantly less GREB1 expression compared to the parental line, suggesting GREB1 expression is lost in hormone-refractory breast cancer cells (16).…”
Section: Discussionmentioning
confidence: 99%